Application Area and Scope of the Principle of Social Risk - Nemetullah Agahabaleı Fanıd (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The administration can only be subjected to financial liability due to its nature and structure as a legal entity. As a requirement of the rule of law principle, the compensation of damages arising from the execution of public services by the administration is evaluated within the theory of "service fault". However, the financial liability of the administration is not limited to service fault. As a requirement of the social state principle, in addition to the principle of balancing the sacrifice, there is also the strict liability of the administration based on the principle of danger or risk. If the administration causes damage while engaging in dangerous activities or using hazardous vehicles, it is held liable even in the absence of fault. Nonetheless, the characteristic that distinguishes social risk liability from the principle of strict liability is that the causal link between the damage and the administrative activity is not sought. The social risk principle ensures that the administration is held strictly liable for damages caused by actions of anarchy and terrorism that disrupt public order.